Notes on Grief - Adichie, Chimamanda Ngozi, 1977- (2021)
On 10 June 2020, the scholar James Nwoye Adichie died suddenly in Nigeria. In this tender and powerful essay, expanded from the original 'New Yorker' text, his daughter, a self-confessed daddy's girl, remembers her beloved father. 'Notes on Grief' is at once a tribute to a long life of grace and wisdom, the story of a daughter's fierce love for a parent, and a revealing examination of the layers of loss and the nature of grief.
Keywords: Adichie, Chimamanda Ngozi, -- 1977- -- Family; Adichie, James Nwoye -- Death and burial; Grief; Fathers and daughters; Family and Relationships